Pengaruh Kepemimpinan Spiritual Kepala Sekolah Terhadap Pembentukan Pribadi Guru dan Penguatan Karakter Siswa Sekolah Dasar - Henderikus Dasrimin; Yoanita Dewi Roswita Kolo Roswita Kolo; Genoveva Lise Dua Kowe; Sturmius Theofanus Lering; Paskalis Nande; Estrado Isaci Selestiano Rodriquez (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to describe the influence of the principal's spiritual leadership on the personal formation of teachers and strengthening the character of elementary school students. This research method uses a descriptive qualitative approach through literature study. The results of this research show that school principals who are imbued with the spiritual leadership model have a positive influence on the personal formation of teachers and strengthening the character of elementary school students.